FENOMENA GLOBALISASI TERHADAP PERKEMBANGAN GERAKAN LGBT DI INDONESIA (2011-2016) - Ariyanti, Dwi Novi; Fachri, Yuli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study discusses the influence of globalization on the development of LGBT (Lesbian,Gay, Bisex, and Transgender) in Indonesia. Indonesia has a history of LGBT development from year to year which is still spelled out surreptitiously. In 2015 the United States constitution adopts same-sex marriage, it becomes a momentum of international LGBT openess. The American decision has influenced other countries to make silimar constitutions and even pave the way for LGBT Asia’s struggle particularly. Indonesia as a member country of the UN is inseparable from the recomendations to accept LGBT. Today this community becomes lifestyle,economic value and trend. Five years back, araund the year 2010 LGBT in Indonesia is still in the concentration of the population as a key transmitter of HIV/AIDS virus, but then the sexual violence that emerged on the surface of children, street children conducted by adult, homosexual in Indonesia is still seen as a crime.This study uses the analysis of querr theory and globalization, which is a method of qualitative research.Key Words: LGBT, History of Indonesian’s LGBT, Globalization, Querr Theory